Pathways to criminalization for street-involved youth who use illicit substances. Issue 5 (19th October 2016) - Boyd, J.; Fast, D.; Small, W.
Abstract: Illicit drug use and homelessness among street-involved young people remain community and public health concerns, in part because of their association with 'public disorder', as well as increased encounters between youth, police, the criminal justice system, and the associated health-related harms. In the public imagination, illicit drug use, homelessness, and police encounters (including incarceration) are often understood as problems rooted in individual biographies. In general, there has been a lack of attention to the larger historical, institutional, and social-spatial contexts that converge across time, to increase young people's risk of coming into contact with police and the criminal justice system. Drawing from a longitudinal ethnography with street-involved young people who use illicit drugs in Vancouver, Canada, we highlight two qualitative case studies that illustrate some of the 'pathways' to criminalization among this population. Specifically, these case studies reflect the complex linkages between child apprehension, foster care, homelessness, illicit substance use, and incarceration (juvenile detention and prison) across time. Our findings highlight the role of state interventions in perpetuating the marginalization that occurs across young people's lives, in ways that increase their vulnerability to police and criminal justice encounters.